2006
DOI: 10.1002/zamm.200510245
|View full text |Cite
|
Sign up to set email alerts
|

Lower semicontinuity and existence of minimizers in incremental finite‐strain elastoplasticity

Abstract: We study incremental problems in geometrically nonlinear elastoplasticity. Using the multiplicative decomposition Dϕ = F el F pl we consider general energy functionals of the formwhich occur as the sum of the stored energy and the dissipation in one time step.Here G(F pl ) is the dislocation tensor which takes the form 1 detImposing the usual constraint det F pl ≡ 1 and suitable growth and polyconvexity conditions on U we show that the minimum of I is attained in the natural Sobolev spaces. Moreover, we are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 53 publications
0
85
0
Order By: Relevance
“…On the one hand we may use the physically more desirable growth rate r = 1 (cf. However, it remains an open problem to generalize our result to the case treated in [MiM06], where only the term G = (curl P )P T is used for regularization. At the moment the best we can do in this direction is to use a regularizing term in the form Ω κ 1 |(curl P )P T | r + κ 0 |∇P | r dx with 0 < κ 0 ≪ κ 1 .…”
Section: Generalizations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand we may use the physically more desirable growth rate r = 1 (cf. However, it remains an open problem to generalize our result to the case treated in [MiM06], where only the term G = (curl P )P T is used for regularization. At the moment the best we can do in this direction is to use a regularizing term in the form Ω κ 1 |(curl P )P T | r + κ 0 |∇P | r dx with 0 < κ 0 ≪ κ 1 .…”
Section: Generalizations and Discussionmentioning
confidence: 99%
“…In [Mie04] it is shown that (1.4) can be solved for arbitrarily large K even without the regularizing terms (∇P, ∇p), but under severe restrictions on W and D. In [MiM06], where the term (curl P )P T is used for regularization, again the solvability of (1.4) is established for more general W and D. Here, we use full regularization via (∇P, ∇p) which is also common in engineering models, cf. [FlH97, Gur00, Gur02].…”
Section: Introductionmentioning
confidence: 99%
“…Let X ∈ C 1 (Ω, M 3×3 ) with X 1 , X 2 , X 3 the rows of X. Then, for the first arrangement, Curl is defined row wise as in [21,31] …”
Section: Preliminary Definitionsmentioning
confidence: 99%
“…Here and subsequently we let o(x), O(x) denote the Landau symbols, respectively, i.e., 20) we conclude with (3.19) and (3.20) that 21) such that…”
Section: Note Added In Proofmentioning
confidence: 99%
“…In contrast to the infinitesimal, the finite strain theory [101,24,54,161,40] deals with several issues such as the existence of the non-unique stress and strain measures, the problem of finding the physically acceptable decomposition of the total deformation into elastic and plastic parts, as well as non-objective material time derivatives of the spatial variables. In order to overcome these issues several different specifications of the rate equations have been considered over time and studied in many papers and books, such as [10,24,69,159,101,161,128]. Accordingly, the finite strain theory is considered to be controversial even though the computational analysis offers the numerical algorithms capable to solve the highly complex problems.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%